Ten apples up on top! - Geisel, Theodor 1904-1991. Theodor Seuss Geisel; McKie, Roy (New York Beginner Books, 1989)
A lion, a dog, and a tiger balance apples on their heads.
D
b
b
Keywords: Animals -- Fiction; Counting; Stories in rhyme